Herpes Simplex Virus Pneumonia: Importance of Aspiration Etiology - Kentaro Odani; Mitsuhiro Tachibana; Rintaro Tamashima; Yutaka Tsutsumi (Case Reports in Pathology)
Herpes simplex virus (HSV) pneumonia caused by aspiration from the oropharyngeal exudates is described. An 89-year-old Japanese male in a poor performance state complained of appetite loss followed by difficulty in swallowing, and bilateral pulmonary infiltrates with interstitial reactions were radiologically pointed out. Antibiotics administration was ineffective, and he died on the 6th day of hospitalization. At autopsy, HSV-induced multiple mucosal erosions were observed on the tongue, pharynx, epiglottis, and trachea. In bilateral lower lobes of the lung, HSV infected bronchiolar and type-II alveolar cells in association with acute interstitial reactions. The infected cells with intranuclear inclusion bodies were immunoreactive with HSV antiserum. HSV-1 infection was confirmed by immunostaining with monospecific monoclonal antibodies and by type-specific real-time polymerase chain reaction. It is very likely that HSV pneumonia was provoked by aspiration of infected exudates from the upper airway (namely, sequential infection from the tongue, epiglottis, and trachea to lung). Oropharyngeal herpes might cause anorexia and difficulty in swallowing, probably accelerating aspiration. The medical staff did not recognize the oropharyngeal lesions of this aged patient. We must realize again the importance of oral care for hospitalized patients to avoid aspiration pneumonia, including herpetic pneumonia.